Validity of MUAC by color-coded tape measure for screening under five undernutrition in post-disaster situations (2007)
The study evaluated the use of the middle-upper arm circumference (MUAC) measured using a color-coded tape as a screening tool in identifying undernourished children in post-disaster situations. Data on weight, height, and arm circumference from 319 children with ages 0 to <60 months old from selected barangays in five disaster-stricken provinces were collected. Validity tests, namely, sensitivity, specificity, predictive value, and percent agreement, were performed using weight-for-height as "gold standard". Results showed that at the prescribed cutoff of 14.0 cm, MUAC by the color-coded tape measure was able to identify as wasted 58% of those children also identified as wasted by weight-for-height. On the contrary, the cutoff of less than 12.5 cm to identify severely wasted children yielded a low sensitivity of 2.5% and a positive predictive value of only 10%, which was significantly improved by increasing the cutoff to less than 13.0 cm. MUAC assessed by the color-coded tape measure is a good screening indicator to diagnose wasting among under five children in post-disaster situations. However, adjustment of the cutoff from less than 13.0 cm to identify severe wasting while maintaining the 14.0 cm cutoff as boundary between wasted and normal individuals is recommended.
Keywords: Nutrition surveys; Child nutrition